UNDERSTANDING BEHAVIOR PATTERNS IN FORENSIC SCIENCE USING NEUROIMAGING TECHNIQUES (Journal of Forensic Medicine & Toxicology, 2025)
The application of advanced brain imaging techniques, such as positron emission tomography , single photon emission computed tomography, and magnetic resonance spectroscopy, has significantly contributed to identifying functional and structural abnormalities in the brain regions involved in aggressive or violent behavior, decision-making, self-control, and reward-seeking conduct. These imaging technologies, in conjunction with psychological assessments, have been employed to compare people exhibiting higher levels of violent/ aggressive behavior with less aggressive individuals. Moreover, research has focused on understanding the neural characteristics of individuals with brain disorders such as psychotic illness, schizophrenia, and antisocial personality disorder. In severe cases, aggression can escalate to criminal acts, both in healthy as well as affected individuals, causing considerable harm to victims and society. This manuscript aims to highlight: (A) current research that integrates brain MR spectroscopic outcome, neuropsychological evaluations, and explores potential associations before the manifestation of violent/ criminal behavior. This approach can improve the understanding of these conditions and potentially identify early predictive signs for early intervention and prevention of such harmful actions, (B) potential brain regions for future investigation, and (C) patterns of neuroimaging outcomes in three distinct categories i.e., non-criminals with brain ailments, criminals with brain ailments, and criminals without brain ailments. In conclusion, our analysis will likely pave a way to identify the broad correlation of neuroimaging outcome with violent behavior.
Keywords: Neuroimaging; Human Behavior; Neural correlates; Psychiatry